AWARENESS, KNOWLEDGE AND THE HEALTH IMPLICATIONS OF ANAEMIA AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINIC IN CENTRAL HOSPITAL, WARRI NIGERIA - Oluwakemi Ajike Kolade RN,; Victoria Funmilayo Hanson RN,; Olayinka Senami Adebiyi RN,; Rachael Egoh RN, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Background: Anemia constitutes a major health challenge globally and has attracted attention towards curtailing its prevalence and it has been established to cause complications during child birth. Aim: The study aimed at investigating the awareness, knowledge and the health implications of anaemia among pregnant women attending antenatal clinic in centralHospital, Warri. Methodology: A descriptive cross sectional survey design using questionnaire adapted from predicting health behavior with social cognition models of MacKian with reliability of Cronbach’s Alpha. 0.71 was used to gather data from 100 pregnant women selected through convenience sampling technique. Data collected wasanalyzed using SPSS version 21.0., regression analysis and Analysis of VarianceResults: Findings revealed that the relationship between awareness and knowledge of anaemia among the pregnant women is significant, however there is no significant difference in level of awareness of anaemia among the pregnant women with socio- demographic characteristics; also there is no significant relationship between the level of awareness and the health ensuring strategies undertaken to curtail anaemia during pregnancy. Conclusion:There is need to increase the level of awareness of anaemia among pregnant women in Warri, Nigeria towards ensuring better health ensuring strategies and prevention of maternal and neonatal morbidity and mortality .